Association of polymorphisms of ACE and AT1R gene with type 2 diabetic nephropathy - CHENG Jie; HUANG Zhong-sheng; LIU Yan-ming; ZHOU Hong-jiu; HUANG Zhi-qing (Linchuang shenzangbing zazhi)
Objective To study the association of angiotensin Ⅰ-converting enzyme(ACE) gene I/D polymorphism and angiotensin Ⅱ receptor type 1(ATIR) A1166 C polymorphism with diabetic nephropathy of Chinese Han people.Methods Patients with type 2 diabetes were selected from Affiliated Hospital of Guangdong Medical University,Dongguan Tangxia Hospital and Ebngguan Dalang Hospital from April 2013 to October 2015.Ninety-seven cases of type 2 diabetes mellitus(T2DM group) and 50 cases of normal control group were enrolled in this study.The T2 DM group was further divided into 52 cases of diabetic nephropathy(DN) subgroup and 45 cases of non-diabetic nephropathy(non-DN) subgroup according to the presence or absence of nephropathy.The peripheral blood DNA was extracted by phenol-chloroform-proteinase K method.The ACEI/D,and ATIR A1166 C polymorphisms were detected by PCR and PCR-restriction fragment length polymorphism respectively.Genetic equilibrium alignment was inspected by Hardy-Weinberg equilibrium method.The correlation between gene polymorphisms and DN was analyzed by chi-square test.Results There was no significant difference in the baseline data between DN and non-DN groups(P>0.05).χ~2 test showed that the DD genotype frequency in DN group[32.6%(17/52)]was significantly higher than in non-DN group[20.0%(9/45)](χ~2 = 6.62,P<0.05),and the D allele frequency in DN group[58.7%(61/104)]was also significantly higher than in non-DN group[41.1%(37/90)](χ~2 = 5.94,P<0.05).There were no significant differences in ATlR Al166 C genotype frequencies between DN group and non-DN group(χ~2 = 0.22,P>0.05),and there were also no significant differences in ATlR Al166 C allele frequencies between DN group and non-DN group(χ~2= 0.21,P>0.05).Statistic analysis did not exhibit significant differences in ACE I/D and ATlR Al166 C genotype and allele frequencies between control group and T2 DM group(P>0.05).Conclusions ACE gene I/D rather than ATlR A1166 C polymorphism was associated with the morbidity of DN in T2 DM of Chinese Han people.DD genotype and D allele of ACE gene may correlate with a predisposing factor for DN.